Crisis Communication Strategy in Managing Complaints Related to Blackout Incidents at Pt Pln (Persero) UID S2JB - Yuni Tiara Sari; Taufik Akhyar; Gita Astrid (Universitas Muhammadiyah Palu, 2026)
This research was motivated by a blackout incident in the work area of PT PLN (Persero) UID S2JB which triggered various negative public complaints on social media and had the potential to reduce public trust in the company. Blackouts are not only a technical nuisance, but also develop into a communication crisis because the public needs fast, clear, and transparent information regarding the cause of the outage and the power restoration process. This study aims to find out the crisis communication strategy of PT PLN UID S2JB in handling complaints about blackout incidents and analyze how negative complaints can trigger a crisis of public trust. This study uses the Situational Crisis Communication Theory (SCCT) theory from W. Timothy Coombs with a qualitative research method. Data collection techniques are carried out through observation, interviews, and documentation. The research informant came from the public relations of PT PLN UID S2JB who was directly involved in handling the blackout crisis communication. The results of the study show that the crisis communication strategy of PT PLN UID S2JB is carried out through the pre-crisis, during crisis, and post-crisis phases. In the crisis phase, the company conveys blackout information through social media, regional stakeholders, and field service units and conducts social media sweeping to monitor public opinion. In the post-crisis phase, the company conducts network evaluation and maintenance as an effort to restore public trust. This research also shows that negative public complaints can develop into a crisis of public trust due to unclear information, delayed communication responses, and the development of negative opinions on social media. Therefore, crisis communication not only functions as an information delivery, but also plays an important role in maintaining the reputation and public trust in PT PLN (Persero) UID S2JB.